Comparison of infantile aggression in two different cultural groups - Roa, María Luisa (2004)
Different emotions and behaviors were examined in this study: Emotional Instability. Physicaland Verbal Aggression, and Prosocial Behavior. First of all, we analyzed the correlation betweenratings from different sources (children or teachers). Cultural differences were also discussedwith regards to a sample of 50 children and adolescents, 25 Peruvians and 25 Spanish.Data showed non-significan! differences in Aggressiveness between children and teachers' ratings.Nevertheless, the correlation is higher between Peruvian children and teachers than betweenSpanish ones. On the other hand, Peruvian teenagers showed higher levels of EmotionalInstability whereas the Spanish got higher average ratings in Prosocial Behavior and Aggressiveness.These data could be due to cultural differences.